Comparison of 3 Methods for Computing Loading Rate during Running - Ueda, T.; Hobara, H.; Kobayashi, Y.; Heldoorn, T. A.; Mochimaru, M.; Mizoguchi, H. (International Journal of Sports Medicine, 2016)
Tibial stress fractures are among the most common and potentially serious overuse injuries in runners. The fractures are thought to be related in part, to excessive loading variables, such as vertical average loading rate (VALR) and vertical instantaneous loading rate (VILR). Although there are several methods for calculating loading rate in running, little is known about the differences between the results produced by these methods. The purpose of this study was to compare 3 previously published methods of calculating VALR and VILR during running. 9 male participants ran on a treadmill at 2.5, 3.0, and 3.5 m/s. VALR and VILR were calculated from vertical ground reaction force using 3 methods that differed by the period over which the loading rates were calculated; foot strike to first peak (method A), from 20 to 80% of the time to first peak (method B), and over the first 50 ms after foot strike (method C). There were significant differences among methods with regard to VALR, but not VILR. Therefore, the results of the present study suggest that VILR is preferable to VALR for consistent evaluation among methods, which make it more acceptable to make study comparisons.
Keywords: tibial stress fracture; running injury; ground reaction force